EVALUATING CULTURAL HERITAGE TOURISM THROUGH A MULTIDIMENSIONAL LENS: METHODS, MODELS, AND THE CASE OF THE GREAT WALL OF CHINA: (Penilaian Pelancongan Warisan Budaya Bangsa Melalui Kaca Mata Multi-Dimensi : Kaedah, Model Dan Kajian Kes Tembok Besar China) (Applied History Journal of Merong Mahawangsa, 2025)
Cultural heritage tourism plays a pivotal role in the preservation of both tangible and intangible heritage while contributing to regional socio-economic development. This study addresses the growing needs to evaluate the multidimensional value of cultural heritage amid rapid tourism expansion. The objective is to systematically review the development of cultural heritage tourism and examine contemporary methods used for heritage value assessment. Methodologically, this research adopts a literature review approach, analyzing domestic and international sources to explore qualitative and quantitative evaluation tools, including Analytic Hierarchy Process (AHP), factor analysis, fuzzy comprehensive evaluation, the Travel Cost Method (TCM), and the Contingent Valuation Method (CVM). Case analyses—particularly the Great Wall Cultural Heritage Corridor and its incorporation into China’s National Cultural Park framework—highlight the evolving practices of integrated conservation, digital engagement, and community participation. Findings reveal a predominance of economic and tangible asset valuation in current literature, with insufficient attention paid to socio-cultural dimensions such as collective memory, identity, and local participation. The paper concludes that sustainable cultural heritage tourism requires a more inclusive and community-centered governance model, alongside innovative strategies such as immersive digital technologies and cross-sector collaboration. This multidimensional and dynamic approach ensures heritage remains a living cultural asset while balancing conservation and development goals.